2019
DOI: 10.21614/chirurgia.114.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hartmann s Reversal: A Single Center Experience

Abstract: RezumatChirurgia colorectalã minimal invazivã prezintã numeroase avantaje în ceea ce priveşte morbiditatea, abordul laparoscopic utilizat în cazul repunerilor în tranzit dupã Hartmann îmbunãtãţind rata de repunere şi evoluţia postoperatorie. A fost analizatã baza de date a Institutului Clinic Fundeni, Departamentul de Chirurgie Generalã, fiind selectate cazurile de refacere a continuitãţii intestinale utilizând laparoscopia. Au fost identificate nouã cazuri, cu vârsta medianã de 63 de ani, cu o medie a BMI-ulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There were only three metaanalysis studies, one of which was based from the results of the American College of Surgeons National Surgical Quality Improvement Program database. [17][18][19] Most retrospective studies included 20 patients [20][21][22][23] ; Park et al investigated 5 patients in particular. 24 Despite the fact that our study included only 66 patients, this was still a major study on laparoscopic reversal of the Hartmann procedure conducted in Asia; furthermore, this is the only study to date that has assessed the safety and advantage of laparoscopic reversal of the Hartmann procedure within the Vietnamese setting.…”
Section: Discussionmentioning
confidence: 99%
“…There were only three metaanalysis studies, one of which was based from the results of the American College of Surgeons National Surgical Quality Improvement Program database. [17][18][19] Most retrospective studies included 20 patients [20][21][22][23] ; Park et al investigated 5 patients in particular. 24 Despite the fact that our study included only 66 patients, this was still a major study on laparoscopic reversal of the Hartmann procedure conducted in Asia; furthermore, this is the only study to date that has assessed the safety and advantage of laparoscopic reversal of the Hartmann procedure within the Vietnamese setting.…”
Section: Discussionmentioning
confidence: 99%
“…A circular-end-to-end anastomosis (CEEA) stapler is inserted transanally. After successful anastomosis, port sites are closed using non-absorbable sutures using the ostomy site approach and involves delayed closure, packing, and secondary intention [13][14][15]. Studies show that patients undergoing laparoscopic colostomy reversal have shown a reduced risk of complication compared to those who underwent OS [1,3,13,[16][17][18].…”
Section: Conventional Laparoscopymentioning
confidence: 99%